Development of digital marketing technologies for promoting educational services of Russian universities in the context of global transformations - V. A. Yudina; M. A. Tanina; V. V. Bondarenko (Вестник университета)
The article substantiates the need to use digital marketing tools to promote Russian educational services to the international educational market. The concept of a marketing information campaign to promote educational services in foreign countries is proposed, which provides for the use of channels and means of interaction with target groups to form an attractive image of the higher education system and encourage foreign applicants to enroll in Russian universities. Conclusions are formulated about the inclusion in the list of works on the development of the information component of the brand promotion of Russian universities of measures for search SEO optimization of university sites, more active use of SMM tools, the use of targeted, contextual advertising, positioning and placement of information on foreign Internet portals.